Simpatico - Bridges, Jeff, 1949-; Stone, Sharon, 1958-; Nolte, Nick.; New Line Home Video (Firm); Emotion Pictures (Firm); Studio Canal+. ([S.l.] : New Line Home Video, 2000)
Three friends share the bond of a crime they committed 20 years ago. When the secret surfaces, it causes greed and passion to erupt. Set in the heart of Kentucky's thoroughbred country.
Special features include: both widescreen and fullscreen versions of the film ; original theatrical trailer ; cast and crew filmographies.
Nick Nolte, Jeff Bridges, Sharon Stone.
Rated R.
DVD; Dolby digital.
Closed-captioned.
Keywords: Feature films; Video recordings for the hearing impaired